1980
DOI: 10.1021/np50010a015
|View full text |Cite
|
Sign up to set email alerts
|

Specioside: A New Iridoid Glycoside From Catalpa speciosa

Abstract: The ethanolic extract of the leaves of Catalpa speciosa with feeding deterrent activity against the gypsy moth larvae was fractionated by solvent partitioning and column chromatography. Two weakly active compounds were isolated and identified by spectral and chemical methods to be catalposide (1) and a new iridoid, specioside (2).A search for naturally occurring antifeeding substances active against the gypsy moth larvae, Lymantria dispar L., revealed that the ethanolic extract of catalpa leaves, Catalpa speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…In 13 C-NMR spectra of 3-8, 10, and 11, fifteen signals for catalpol were detected with similar chemical shift values (Table I. (3), amphicoside (6), catalposide (7), and verproside (10) by comparison of spectral data with published data in the literatures (El-Naggar and Beal, 1980;Sticher and Afifi-Yazar, 1979;Iwagawa et al, 1990;Gao et al, 2003;El-Naggar and Doskotch, 1980;Afifi-Yazar and Sticher, 1980). Phenylpropanoid moieties for compounds 4, 5, 8, and 11 were identified from their spectral data as isoferuloyl, trans-p-coumaroyl, cis-pcoumaroyl, and caffeoyl groups, respectively.…”
Section: Resultssupporting
confidence: 54%
“…In 13 C-NMR spectra of 3-8, 10, and 11, fifteen signals for catalpol were detected with similar chemical shift values (Table I. (3), amphicoside (6), catalposide (7), and verproside (10) by comparison of spectral data with published data in the literatures (El-Naggar and Beal, 1980;Sticher and Afifi-Yazar, 1979;Iwagawa et al, 1990;Gao et al, 2003;El-Naggar and Doskotch, 1980;Afifi-Yazar and Sticher, 1980). Phenylpropanoid moieties for compounds 4, 5, 8, and 11 were identified from their spectral data as isoferuloyl, trans-p-coumaroyl, cis-pcoumaroyl, and caffeoyl groups, respectively.…”
Section: Resultssupporting
confidence: 54%
“…The LC was coupled to a LCT of a TOF MS (Micromass, Manchester, UK) operated in the positive electrospray ion mode using 5-leucineenkephalin as lock mass. The known compounds isolated were identified by their NMR data: mannitol (21), (Bock and Pedersen, 1983); and iridoids (1-4, 6, 11) (Rønsted et al, 2000); erinoside (5) (Taskova et al, 2005); sinuatol (10; 6-O-rhamnopyranosylaucubin) ; verproside (12) (Afifi-Yazar and Sticher, 1980); specioside (13) (El-Naggar, and Doskotch, 1980); verminoside (14) and minecoside (15) (Sticher and Afifi-Yazar, 1979); 6-O-rhamnopyranosylcatalpol (16) (Helfrich and Rimpler;1999); scrophularioside (19) ; persicoside (22) (Harput et al, 2002); epiaucubin (Bianco et al, 1983);…”
Section: Generalmentioning
confidence: 99%
“…Evidence from other studies has suggested that iridoid glycosides might be important in feeding preferences of L.dispar. For example, El-Nagger & Doskotch (1980) isolated two iridoid glycosides, specioside and catalposide, from leaves of Catalpa speciosa Warder (Bignoniaceae), and suggested that t k s e compounds were responsible for an earlier finding ) that extracts of Cspeciosa were deterrent to gypsy moth larvae. Four other iridoid glycosides, aucubin, catalpol, loganin and asperuloside, significantly reduced growth of gypsy moth larvae when incorporated into artificial diets at levels of 0.2% , suggesting that iridoid glycosides reduced diet suitability.…”
Section: Introductionmentioning
confidence: 99%